2021
DOI: 10.1007/s11325-021-02399-9
|View full text |Cite
|
Sign up to set email alerts
|

Estimated respiratory arousal threshold in patients with rapid eye movement obstructive sleep apnea

Abstract: Purpose Rapid eye movement (REM) obstructive sleep apnea (OSA) is a prevalent clinical phenotype. However, the literature focusing on the pathophysiology of REM OSA is limited. This study compared the proportion of individuals with a low respiratory arousal threshold between patients with REM and non-REM OSA. Methods REM OSA was defined as having an apnea–hypopnea index (AHI) ≥ 5 and AHI during REM (AHI-REM)/AHI during NREM (AHI-NREM) ≥ 2. REM OSA was sub-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 13 publications
(23 reference statements)
0
4
1
Order By: Relevance
“…Moreover, Hoshino et al reported a low respiratory arousal threshold in patients with REM OSA than in those with non-REM OSA. 30 In the current study, although the arousal index in the enrolled patients with REM OSA was lower than that in patients with non-REM OSA before treatment, sympathetic tone might have been elevated in patients with REM-OSA. This in turn might have affected the progression of arterial stiffness.…”
Section: Discussioncontrasting
confidence: 55%
“…Moreover, Hoshino et al reported a low respiratory arousal threshold in patients with REM OSA than in those with non-REM OSA. 30 In the current study, although the arousal index in the enrolled patients with REM OSA was lower than that in patients with non-REM OSA before treatment, sympathetic tone might have been elevated in patients with REM-OSA. This in turn might have affected the progression of arterial stiffness.…”
Section: Discussioncontrasting
confidence: 55%
“…(2020) conducted a study on a large group of participants and found a significant association between REM‐related OSA and increased Pittsburgh Sleep Quality Index (PSQI) scores in all adjusted models. The same group also discovered that patients with REM‐related OSA have a lower arousal threshold, which prevents them from reaching the deeper sleep stage where stable breathing is observed (Hoshino et al., 2022). The two conditions that are reported frequently in this phenotype could amplify the aforementioned process through oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, ventilatory overshoot during arousal’s opening of the UA lowers the PaCO 2 (and thus ventilatory stimuli for airway opening), promoting the recurrence of UA collapse [ 42 ]. A low ArTH is more common in individuals with REM-dependent OSA [ 44 ], and among those who are non-obese, older, and taking antidepressants [ 45 ]. Individuals with post-traumatic stress disorder may also have a lower ArTH, presumably due to their hyperadrenergic state [ 46 ].…”
Section: Osa Traitsmentioning
confidence: 99%